PENGARUH HOAKS TERHADAP STABILITAS NASIONAL: PERSPEKTIF PENDIDIKAN KEWARGANEGARAAN - Desi Devrika Devra (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
The spread of hoaxes has become a serious threat to national stability in the digital era. Hoaxes not only disinformation but also contribute to social disintegration, political polarization, horizontal conflict, and economic panic. This study aims to analyze the impact of hoaxes on various aspects of national life and explore the role of Civics Education (PKn) in addressing these threats. Using a descriptive qualitative approach, data were obtained through a literature review of academic sources and government policies. The study results indicate that hoaxes can undermine public trust in state institutions and lead to multidimensional instability. On the other hand, PKn plays a strategic role in equipping citizens with digital literacy, Pancasila values, and critical and ethical attitudes in media use. By integrating digital literacy into the PKn curriculum, society can be more resilient to attacks of false information. This study recommends strengthening character education and legal understanding through PKn to create informed and socially responsible citizens.